Analisis Pengawasan Kepala Terminal untuk Optimalisasi Fungsi Terminal Sumber di Kabupaten Cirebon - Ria Apriliyani Putri; Rahmat Hidayat; Siti Khumayah (Jurnal Ilmiah Publika, 2014)
ABSTRACT The research that the writer did was about "Analysis of Supervision of the Head of the Terminal to Optimize the Function of Source Terminals in Cirebon District". Based on observations made by the author at the Cirebon Regency Source Terminal, there are symptoms that indicate that the Terminal Sumber function is not yet optimal as there are still many transporters who raise and lower passengers outside the terminal and the low number of public transport entering the terminal. These problems are caused by the lack of direct inspections and corrective actions in indirect supervision carried out by the Head of the Cirebon Regency Source Terminal.            Based on the above problems, the writer identifies the problem as follows: How to supervise the Head of the Terminal to optimize the function of the Source Terminal in Cirebon Regency and the Factors that support the supervision of the Head of the Terminal and Obstacles in the supervision of the Head of the Terminal to optimize the function of Source Terminals in Cirebon Regency.The supervision theory used is the theory of Sondang P. Siagian (2003: 115) which consists of direct supervision including direct inspection, on-the-spot observation, on-the-spot report. and indirect supervision including written reports and oral reports.            The method I use is descriptive survey research method using a qualitative approach, by taking the location of research at the Cirebon Regency Source Terminal, while the informant in this study is the Head of the Source Terminal, the Head of Terminal and Parking of the Transportation Department of Cirebon Regency, the officers at Sumber Terminal, public transport drivers and public transport passengers.In this study, it was obtained the results that the supervision of the Head of the Terminal to optimize the function of the Source Terminal in Cirebon Regency was not optimal, as seen from the fact that there were no sanctions in the Regional Regulations for officers who made mistakes or the drivers of Transportation who violated, also where the quantity or number of officers in the field still lacking, the number of passengers who switched to using private vehicles and the existence of a cator (motor tricycle), from facilities and infrastructure still inadequate, far from being feasible and comfortable.